2011
DOI: 10.1021/am2008322
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasmall Hollow Gold–Silver Nanoshells with Extinctions Strongly Red-Shifted to the Near-Infrared

Abstract: Hollow gold-silver nanoshells having systematically varying sizes between 40 and 100 nm were prepared. These particles consist of a hollow spherical silver shell surrounded by a thin gold layer. By varying the volume of the gold stock solution added to suspensions of small silver-core templates, we tailored the hollow gold-silver nanoshells to possess strong tunable optical extinctions that range from the visible to the near-IR spectral regions, with extinctions routinely centered at ∼950 nm. The size and morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
90
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 67 publications
(105 reference statements)
3
90
0
Order By: Relevance
“…Using a replacement reaction [7], the formation of Ag-Au nanoshells was achieved by adding the K-gold solution to PLGA@Ag nanocolloids. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a replacement reaction [7], the formation of Ag-Au nanoshells was achieved by adding the K-gold solution to PLGA@Ag nanocolloids. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As the Au 0 continued to deposit onto the exterior of Ag NPs, Au nanoshells began to form. As the reaction proceeded, a porous bimetallic Ag-Au nanoshell was produced on each PLGA NP [7]. A UV-vis absorption spectrum of PLGA@Ag-Au NPs is shown as Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, noble metal nanoparticles, exhibiting NIR absorption in the appropriate size regime (20-100 nm) for biological applications, are modified with either an antibody or ligand specific to an antigen or receptor, on the surface of a tumor cell [38,53,190]. NIR absorbing particles are preferred since it is well known that blood and tissue are most readily penetrated by light in this wavelength region [191][192][193]. The bioconjugated nanoparticles are then introduced, either in vitro or in vivo, and allowed to incubate or circulate and bind to the tumor site.…”
Section: Photothermal Ablation (Pta) Therapymentioning
confidence: 99%
“…Typically penetration in the range of 1-20 mm is sufficient for the ablation of cancer cells that are near the surface of the skin [160,191,193,204]. However, it has been reported that depths of 50-80 mm have been achieved [186,205].…”
Section: Photothermal Ablation (Pta) Therapymentioning
confidence: 99%